Green Extraction Strategies for Sea Urchin Waste Valorization - Marzorati, Stefania; Martinelli, Giordana; Sugni, Michela; Verotta, Luisella (Frontiers in Nutrition, 2021)
Commonly known as “purple sea urchin”, Paracentrotus lividus occurs in the Mediterranean Sea and eastern Atlantic Ocean. This species is a highly appreciated food resource, being Italy the main consumer among the European countries. Gonads are the edible part of the animal but they represent only a small fraction (10-30%) of the entire sea urchin mass, therefore the majority ends up as a waste. Recently, an innovative methodology was successfully developed to obtain high-value collagen from sea urchin by-product tissues to be used for tissue engineering. However, tissues used for collagen extraction are still a small portion of the sea urchin waste (less than 20%) and the remaining part, mainly the carbonate-rich test and spines, are discarded. Residual cell tissues, tests and spines, contain polyunsaturated fatty acids, carotenoids and a class of small polyphenols, called polyhydroxynaphthoquinones (PHNQ). PHNQ, due to their polyhydroxylated quinonoid nature, show remarkable pharmacologic effects and have high economic significance and widespread application in several cosmetic and pharmaceuticals applications. A green extraction strategy aimed to obtain compounds of interest from sea urchins’ waste was developed. The core strategy was supercritical CO2 technique, characterized by low environmental impacts. Fatty acids and carotenoids were successfully and selectively extracted and identified depending on the physical parameters of the supercritical CO2 extraction. Finally, the exhausted powder was extracted by solvent-based procedures to yield PHNQ. The presence of Spinochrome A and Spinochrome B was confirmed and extracts were characterized by a remarkably high antioxidant activity, measured through the ABTS assay. Overall, selective and successive extraction methods were validated for the valorization of waste from sea urchins, demonstrating the feasibility of the techniques targeting added-value compounds.